Prevalence and determinants of depression among community- dwelling older adults with chronic diseases - Mulud, Zamzaliza Abdul; Mohamad, Norfidah (Intelektual Pustaka Media Utama, 2023)
The older population continues to grow globally, and data related to the prevalence of depressive symptoms among this population in Malaysia is scarce. Thus, this study aimed to determine the prevalence and determinants of depression symptoms among community-dwelling older adults in Malaysia. A cross-sectional study was conducted among 220 outpatients with chronic diseases. The level of depression was operationalized using the Malay version of the Geriatric Depression Scale. The prevalence of depression among community-dwelling older adults was 16.4%. Female (OR =8.86, 95% CI=1.10–7.53, p=0.03), Chinese ethnic group (OR=4.73, 95% CI= 1.04– 21.48, p=0.04), multimorbidity (OR=3.36, 95% CI=1.07–12.60, p=0.04) and presence of pain (OR=6.67, 95% CI=2.41–18.45, p<0.01) were associated to depressive symptoms. However, higher resilience was associated with lower risk of depressive symptoms in this population (OR=0.88, 95% CI=0.88–0.93, p<0.01). The prevalence of depressive symptoms among older adults with chronic diseases is higher than in previous data. Early identification of depression in this population is crucial for effective chronic disease management.